Prevalence of and Risk Factors for Trachoma in Southern Nations, Nationalities, and Peoples' Region, Ethiopia: Results of 40 Population-Based Prevalence Surveys Carried Out with the Global Trachoma Mapping Project. (7th December 2016) - Adera, Tesfaye Haileselassie; Macleod, Colin; Endriyas, Misganu; Dejene, Michael; Willis, Rebecca; Chu, Brian K.; Letamo, Yohannes; Misganaw, Tebeje; Mesele, Tamiru; Mekonnen, Emebet; Sisay, Alemayehu; Mulugeta, Yeneneh; et al.
ABSTRACT: Purpose : We sought to estimate the prevalence of trachoma at sufficiently fine resolution to allow elimination interventions to begin, where required, in the Southern Nations, Nationalities, and Peoples' Region (SNNPR) of Ethiopia. Methods : We carried out cross-sectional population-based surveys in 14 rural zones. A 2-stage cluster randomized sampling technique was used. A total of 40 evaluation units (EUs) covering 110 districts ("woredas") were surveyed from February 2013 to May 2014 as part of the Global Trachoma Mapping Project (GTMP), using the standardized GTMP training package and methodology. Results : A total of 30, 187 households were visited in 1047 kebeles (clusters). A total of 131, 926 people were enumerated, with 121, 397 (92.0%) consenting to examination. Of these, 65, 903 (54.3%) were female. In 38 EUs (108 woredas), TF prevalence was above the 10% threshold at which the World Health Organization recommends mass drug administration with azithromycin annually for at least 3 years. The region-level age- and sex-adjusted trichiasis prevalence was 1.5%, with the highest prevalence of 6.1% found in Cheha woreda in Gurage zone. The region-level age-adjusted TF prevalence was 25.9%. The highest TF prevalence found was 48.5% in Amaro and Burji woredas. In children aged 1–9 years, TF was associated with being a younger child, living at an altitude <2500m, living in an area where the annual mean temperature was >15°C, and the use of open defecation by household members. Conclusion : Active trachoma and trichiasis are significant public health problems in SNNPR, requiring full implementation of the SAFE strategy (surgery, antibiotics, facial cleanliness, and environmental improvement).